Wielkie zgromadzenie publiczne. (Gdańsk : [s.n.], 1947)
Afisz inform. o zgromadzeniu z udziałem Władysława Dworakowskiego w Sali Stoczni nr 1 25.01.1947 r.
Keywords: Dworakowski, Władysław -- (1908-1976).; Stocznia Gdańska -- 1945-1970 -- druki ulotne